Pengaruh Core Stability Exercise Terhadap Keseimbangan Berjalan Pasien Pasca Stroke di RSU Gunung Maria Tomohon - Vione D. O. Sumakul; Youla Agnes Lontaan (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2023)
Walking balance disturbance in stroke patients is associated with to inability to regulate body movement and muscle mobility. Patients with stroke have problems with postural control and it will have an impact in decreasing muscle function including the lower extremities. There are several non-pharmacological treatments that can be used, one of that is by intervening in core stability exercise. This research aimed to determine the effect of core stability exercise on the walking balance to the post- stroke patients.This type of the research was pre-experimental using the one group pre-post-test design. The sampling technique used was a Consecutive sampling with sample of 20 respondents who were given core stability exercise for 4 weeks with exercise 3 times a week. Data collection uses POMA observation sheets (Tinetti Performance Oriented Mobility Assessment). The test statistic used was the Wilcoxon statistical test and the value ρ = 0,000 obtained with a significance level of α = 0.05. This shows ρ ˂ α, which means that Ho was rejected and Ha was accepted. The results of this research indicated that core stability exercise can improve the walking balance of post-stroke patients.